Science, technology and innovation for sustainable urbanization - Ok, Tansug (UN New YorkUS, 2015)
Aims to contribute to the sustainable urbanisation discourse by addressing the specific role of science, technology and innovation, based on literature review and an analysis of cities in developed and developing countries that provide examples that can be reapplied elsewhere.